Effectiveness of Incentive and Disincentive Programmes as a Waste Management Strategy in Sleman District - Denny Margianto; Hanantyo Sri Nugroho (Jurnal Partisipatoris, 2025)
This research examines waste management in Sleman Regency. This problem is interesting to research because due to the lack of waste management carried out by the government. The task of the Sleman Regency government is to invite the community to participate in incentive and disincentive programs. Providing incentives and disincentives according to the needs of the community is expected to influence waste management in Sleman Regency by using the participation of the community itself. Therefore, this research is intended to determine the effectiveness of the incentive and disincentive program of the local government of Sleman Regency as a waste management strategy. To examine these problems, researchers used the theory of program effectiveness according to Van Meter and Van Horn. This study uses descriptive qualitative methods through observation, interviews, and documentation studies. The results of the study show that the incentive and disincentive program is a waste management strategy in Sleman Regency, because it meets the existing criteria and implementers and other waste management parties say that this program helps in waste management. From this research, it was found that the driving factors in the success of this program include this program being accepted by many parties and flexible program implementation. There are also inhibiting factors in running this program including this program has not been structured in detail and has not been well socialized to the community, and there is also no special unit tasked with incentives and disincentives as a waste management strategy in Sleman Regency.